Studi Efek Semprotan Serangkaian Nosel Pada Cerobong Terhadap Profil Kecepatan Dan Temperatur Dengan Metode CFD - Jamaldi, Agus, Ir. Sarjito, MT.,Ph.D, Marwan Effendy, ST.,MT.,Ph.D (2016)
The decrease of temperature in the evaporation chimney could be achieved by adding water spray system inside the chimney. This paper describes a simulation research in order to investigate the influence of the nozzle configuration and the level of humidity to the velocity profile and temperature distribution inside the chimney. This research was performed computationally by applying k-ε turbulence model. Geometry of chimney and nozzle used by other researcher in the previous simulation, including their finding data, were chosen as a standard design during mesh refinement study and validation stage, hereinafter was modified in terms of nozzle configurations inside the chimney. The profile of velocity and temperature were observed along the investigation. The results show that the validation data is consistent to the previous study. The configuration, with 8 nozzles at a height of 3.94 m and 4 nozzles at a height of 3.5 m from the base of the stack, produces an optimum level in terms of the decrease of temperature and the velocity of vapour.